2007
DOI: 10.1016/j.exer.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the bioavailability of thioredoxin in the lens by a specific thioredoxin-binding protein (TBP-2)

Abstract: Thioredoxin (TRx) is known to control redox homeostasis in cells. In recent years, a specific TRx binding protein called thioredoxin binding protein-2 (TBP-2) was found in other cell types and it appeared to negatively regulate TRx bioavailability and thereby control TRx biological function. In view of the sensitivity of lens transparency to redox status, proper regulation of TRx bioavailability is of the utmost importance. This study was conducted to examine the presence and function of TBP-2 in human lens ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Despite the demonstration that TXNIP inhibits TRX activity in multiple cell types in vitro including ECs, 10 vascular smooth muscle cells, 20 breast cancer cells, 21 lens epithelial cells 94 and mesangial cells, 95 and in aortic tissue ex vivo 91 this observation has not been consistently demonstrated in vivo . This is particularly true of the total and tissue-specific TXNIP knockout mice, 22, 23, 96, 97 and TXNIP-deficient mouse models available, 98 which demonstrate no significant changes in TRX activity.…”
Section: The Thioredoxin Systemmentioning
confidence: 93%
“…Despite the demonstration that TXNIP inhibits TRX activity in multiple cell types in vitro including ECs, 10 vascular smooth muscle cells, 20 breast cancer cells, 21 lens epithelial cells 94 and mesangial cells, 95 and in aortic tissue ex vivo 91 this observation has not been consistently demonstrated in vivo . This is particularly true of the total and tissue-specific TXNIP knockout mice, 22, 23, 96, 97 and TXNIP-deficient mouse models available, 98 which demonstrate no significant changes in TRX activity.…”
Section: The Thioredoxin Systemmentioning
confidence: 93%
“…TXNIP fulfills many functions, including negative regulation of mammalian target of rapamycin (mTOR) complex 1 (Jin et al, 2011), activation of the NACHT, LRR and PYD domains-containing protein 3 (NLRP3) inflammasome (Zhou et al, 2010) and inhibition of the antioxidant enzyme TRX (Nishiyama et al, 1999). The latter function is associated with higher susceptibility to oxidative stress (Liyanage et al, 2007), which again links UPR signaling with oxidative challenge.…”
Section: Crosstalk To Map Kinases and Antioxidant Pathwaysmentioning
confidence: 99%
“…Trx1 is present in the lens and has been demonstrated to be an effective oxidation defense enzyme [23]. TBP-2 is also present in the lens, and under oxidative stress it has been shown to regulate the bioavailability of Trx [24]. Furthermore, it was shown that human lens epithelial B3 (HLE B3) cells with over-expressed TBP-2 displayed lower Trx activity, slower cell growth and increased susceptibility to H 2 O 2 -induced apoptosis [24].…”
Section: Introductionmentioning
confidence: 99%
“…TBP-2 is also present in the lens, and under oxidative stress it has been shown to regulate the bioavailability of Trx [24]. Furthermore, it was shown that human lens epithelial B3 (HLE B3) cells with over-expressed TBP-2 displayed lower Trx activity, slower cell growth and increased susceptibility to H 2 O 2 -induced apoptosis [24]. However, little is known about the mechanism responsible for slow cell growth, and the accelerated H 2 O 2 -induced apoptosis in cells enriched with TBP-2.…”
Section: Introductionmentioning
confidence: 99%